(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Plants oil are becoming important in commerce and nutrition worldwide as they are good source of dietary energy and raw material for the manufacture of industrial products. Despite this fact little attention has been given to Balanites aegyptiaca oil. Therefore there is growing interest in understanding the potential of Balanites aegyptiaca oil as feedstock for improving livelihoods of communities in dryland areas. Balanites aegyptiaca is a multipurpose tree species in dry land of Africa. The plant seed kernel produces high quality oil that amounts for 9-10 % by weight of the whole fruit. Its seed kernel has high oil content (50 %) whose extraction is economically worthwhile. The oil parameters revealed that the oil composed of long chain fatty acids with high degree of unsaturation, making it a good feedstock for biodiesel production. It also has biologically active properties which contribute in its medicinal application. The oil is fulfilling in saturated fatty acids, as such are accustomed as cooking oil. Balanites aegyptiaca oil may be useful for industrialists that produce eco-friendly soap. Therefore, conversion of the oil to different products will help in domestication of this neglected and underuse dryland tree species. This may advocate wise use of renewable natural resources and not protection without possible economic benefit. Thus, Balanites aegyptiaca oil is a multipurpose feedstock with high economic potential and industrial applications if richly exploited. Furthermore, many prospective exploitation possibilities will emerge when further researches are made on this multipurpose oil.